Efeitos do treinamento do método Pilates com aparelhos sobre a pressão arterial e a função pulmonar de mulheres hipertensas - Araujo, Rebeca Marília de Alcantara (2017)
Introduction: In order to reduce and control blood pressure, it is indicated as non-pharmacological treatment the practice of physical exercise that can be considered an effective, safe and inexpensive way. In front of the types of training you can highlight the Pilates method. Purpose: To evaluate the effect of Pilates method on systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), body fat percentage and force vital capacity (CVF) of hypertensive women. Methods: Twenty-six women, eight normotensive (C), 10 hypertensive controls (HC), and eight decompensated hypertensives (HD), aged 50 to 65 years, underwent 12 weeks of Pilates, two weekly sessions lasting 60 minutes each. The protocol consisted of 10 exercises performed in specific equipment, three sets of 10 repetitions and one-minute interval between sets. SBP, DBP, MAP, body far percentage and FVC were measured 48 hours before and 48 after the training period. Results: Pilates promoted reduction in SBP (9 mmHg) and MAP (7 mmHg) in the HD group, DBP did not change in any of the groups. Pilates also reduced the percentage of fat in the groups of controlled hypertensive and decompensated hypertensives (HC: before: 28±3; after: 26±3; HD: before: 24±5; after: 23±4%). The arterial hypertension decreased the FVC, regardless of the pressure condition, even after 24 training sessions. Conclusion: It was possible to verify that 24 training sessions of Pilates method with devices, with moderate intensity reduce blood pressure and percentage of body fat in hypertensive women who did not have BP in normal values. Pulmonary function had a decrease in hypertensive groups and Pilates did not reverse this condition.